PENGARUH EFEKTIVITAS PENGGUNAAN DAN KEPERCAYAAN TEKNOLOGI SISTEM INFORMASI TERHADAP KINERJA KARYAWAN BANK RAKYAT INDONESIA CABANG RANTEPAO - Biringkanae, Astriwati (STIE Muhammadiyah Tanjung Redeb, 2019)
Information system is seen as one of the factors of competitive advantage for an organization or company. This research aimed at investigating and analyzing: (1) the influence of the use effectiveness of the information system technology on the employees performance, (2) the effect of the use effectiveness of the information system technology on the information system technology trust, (3) ) the influence of the trust of the information system technology on the employees performance, (4) the effect of the use effectiveness through the trust of the information systems technology on the employees performance. The research used the causal explanatory design. The research was conducted in Bank Rakyat Indonesia of Rantepao Branch and carried out in the early month of October 2016. The research population was the employees of Bank Rakyat Indonesia of Rantepao branch as many as 100 people. Samples were selected using the probability sampling technique. The data were analyzed using the instrument of the statistic application software of SPSS 22. The research result indicates that: (1) the use effectiveness of the information system technology having the influence on the employees performance is acceptable, (2) the use effectiveness of the use of the information system technology on the trust of the information systems technology is acceptable, (3) the trust on the information system technology having the positive and significant effect on employees performance is acceptable, (4) the use effectiveness of the information system technology having the positive and significant influence on the employees performance of Bank Rakyat Indonesia of Rantepao Branch through the trust on the information systems technology is acceptable.